EXAMINATION OBJECTIVES. - Boyd, Ralph L. (The Accounting Review, 1943)
Abstract Almost all the states at present require examination in the subjects of accounting theory, accounting practice, auditing, and law. In some states separate examinations are given in each subject. In many others accounting theory and practice are combined as one for grading purposes even though the examination is given in two parts. In still other states, subject matter from all these fields is included in the examination given, although not separately listed in the same four divisions. A few states give examinations in these subjects and additional examinations in other subjects. Since forty-six of the fifty-two states and territories use the American Institute of Accountants' examination questions, it may be said that the stated objective with reference to subject matter is now substantially reached. Laws and regulations, however, do not reveal the extent to which uniformity actually exists. Reference to the four general subjects is made either by law or regulation (mainly in the law itself) in forty-six states. Many refer to the combination of accounting theory and practice as one subject; a few refer to the use of American Institute examination questions; some list the four major subjects and also state that other subjects will be covered if deemed necessary or desirable by the board.